PERANCANGAN ALAT KERJA PADA PROSES PENCETAKAN TAHU DI UKM AWI SAGUBA - Warman, Ricky; Sirait, Ganda (LPPM Universitas Putera Batam, 2022)
The job of people as still affects each modern movement. People as laborers actually have restricted capacities so they are not the same as machines that can be supplanted and fixed. Manual work exercises and work that is done over and over have a high gamble of MSDs grievances brought about by manual work devices. Tofu printing exercises at the Tahu Awi Saguba UKM during the tofu printing process can possibly cause MSDs risk since it is completed physically, over and over with an unselfish stance and straightforward work devices. This study started with the computation of the Nordic Body Map survey where the consequences of this poll showed objections of right lower leg, left lower leg, right wrist, left wrist, upper left arm, right upper arm, right shoulder, left shoulder. These outcomes show that the work risk score with REBA has a normal of 6 where this number is ordered as moderate and restorative activity is required. With an end goal to limit this gamble, a print machine configuration was carried out by carrying out the EFD technique. The aftereffects of the print machine configuration in light of ergonomic angles, specifically: Successful, Agreeable, Protected, Solid, Proficient (ENASE). By focusing on the plan of the print machine, it limits torment for workers who have a weight (0.333) as well as the objective detail of the print machine. Planned in view of laborer anthropometry. The anthropometric information utilized are LB (Shoulder Width), TSB (Standing Elbow Level), GT (Hand Hold).